Konflik Antara Alam dengan Manusia dalam Novel Hujan Karya Tere Liye : Suatu Kajian Ekokritik Gerg Gerrard - Rika Febri Finansyah; Mahda Annida Mufasyaroh; Veny Fitriana Rahman; Ardheta Bintang Rahmadena; Moh Raji (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This paper examines the conflict between nature and humanity in Tere Liye’s novel “Hujan” using the ecocritical approach proposed by Greg Garrard. The study focuses on how human actions impact the environment and how nature responds to these actions. Employing a qualitative descriptive method, data was collected from the novel’s text and analyzed using ecocritical theory. The analysis reveals that the novel depicts various forms of pollution, habitat destruction, and the catastrophic consequences of unsustainable human exploitation of nature. 1 Pollution resulting from the use of environmentally unfriendly energy sources and harmful environmental policies emerges as the central theme. Additionally, the novel portrays the decline of wilderness areas as sources of ecosystem balance and biodiversity due to destruction. Ecological disasters, both natural and human-induced, give rise to conflicts between human needs and the carrying capacity of natural resources. By emphasizing the reciprocal relationship between humans and the environment, this study aims to raise awareness about the importance of environmental conservation through the lens of literature.